Boosting E-Commerce Financial Performance with QuickPack: An Android-Based Packer Tracking Solution - Memarista, Gesti; Oden, Nicholas (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2025)
Abstract. The COVID-19 pandemic has emphasized the need for financial performance improvement, especially in Indonesia’s rapidly growing e-commerce sector. Manual processes are time-consuming and error-prone, making it difficult to reward productivity effectively. This study develops QuickPack, an Android Studio-based app to track packers in an online shop, enhancing efficiency through automation technology. Using the Waterfall model, Firebase, and Kotlin, QuickPack provides real-time performance tracking. Researchers applied qualitative methods, observing and interviewing packers, managers, and owners before and after implementation. The app offers features like user registration, receipt tracking, daily monitoring, performance reporting, and target setting. Results show a 63% financial performance boost and an 80-90% speed increase on peak days. QuickPack reduces labor costs, minimizes errors, improves productivity, and streamlines operations, lowering the need for additional staff. Monetization opportunities, such as premium tracking services, further enhance revenue. Improved security also mitigates fraud risks. Modernizing operations, QuickPack increases revenue, reduces financial risks, and enhances job satisfaction through transparent performance tracking. Successfully developed and tested, the app improves packing efficiency and strengthens financial performance for online shops. Keywords: QuickPack application, e-commerce, automation technology, financial performance, performance tracking